2020
DOI: 10.2478/pjct-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Selected magnesium compounds as possible inhibitors of ammonium nitrate decomposition

Abstract: AbstractAmmonium nitrate (AN) is considered to be a very hazardous and difficult to handle component of mineral fertilizers. Differential thermal analysis coupled with thermogravimetry and mass spectrometry was used to determine the possible inhibiting effect of selected magnesium compounds on thermal decomposition of AN. Each additive was mixed with AN to create samples with AN:magnesium compound mass ratios of 4:1, 9:1 and 49:1. Most of analyzed compounds enhanced thermal sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Since the exothermic decomposition is the main focus of this study, only DTA-TG results were described in detail and included in Table 2 containing all parameters used for the thermal stability assessment of analyzed samples. Even though the exothermic decomposition process of ammonium nitrate has already been defined in previous work [46,48], authors deemed it necessary to provide an extensive discussion of obtained results to provide readers with all crucial information. As the thermal stability assessment is mainly comparative and the pure AN sample is used as a reference, DTA-TG and MS results obtained during the measurement of the pure AN sample were described below and presented in Fig.…”
Section: Ammonium Nitratementioning
confidence: 99%
“…Since the exothermic decomposition is the main focus of this study, only DTA-TG results were described in detail and included in Table 2 containing all parameters used for the thermal stability assessment of analyzed samples. Even though the exothermic decomposition process of ammonium nitrate has already been defined in previous work [46,48], authors deemed it necessary to provide an extensive discussion of obtained results to provide readers with all crucial information. As the thermal stability assessment is mainly comparative and the pure AN sample is used as a reference, DTA-TG and MS results obtained during the measurement of the pure AN sample were described below and presented in Fig.…”
Section: Ammonium Nitratementioning
confidence: 99%
“…Incorporation of CF does not alter the phase transition peaks and the melting point of ammonium nitrate; however, the decomposition of ammonium nitrate is impacted, which occurs at a lower temperature in the presence of CF, signifying the CF's role in facilitating the decomposition process of ammonium nitrate. In previous studies, 21,24,25 it was reported that the incorporation of additives like metal ion salts can alter all curves, including the phase transition, melting temperatures and decomposition temperatures of ammonium nitrate. In our study, we observed that CF exclusively affects the decomposition peak of ammonium nitrate.…”
Section: Paper Materials Advancesmentioning
confidence: 99%
“…In yet another study, the authors documented that the presence of magnesium chloride led to the decomposition of ammonium nitrate with a maximum decomposition temperature of 268.8 ± 2.3 °C, while the presence of potassium chloride resulted in a reduction of the maximum decomposition temperature to 261.1 ± 2.3 °C, occurring within a broad temperature range. 24,25…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation